“The Greater the Disposition, The Closer to Collaboration”: English Teaching Strategies Mediated by Music Enhance a Positive and Collaborative Learning Environment (2023)
A notable tendency is perceived in English teachers attached to formal education in Colombia in terms of planning their classes based on grammar, avoiding or dodging innovative solutions that respond to the student's context (Echeverri Sucerquia & Sierra Piedrahíta, 2019). Due to this, the Ministry of National Education [MEN] has proposed English teaching strategies to motivate and support their action, despite the reluctance to change (Díaz Laínes & Santana Sanabria, 2020), these awareness processes. The present study aimed to examine the implementation of English teaching strategies mediated by music to create a positive and collaborative learning environment to improve teachers' didactics. To accomplish this purpose, qualitative research standards were adopted, and a niche population that belongs to a private educational institution in Medellín, Colombia, was chosen. The data were analyzed through an inductive and deductive process, dividing the information into codes and categories. Results indicated that the introduction of music helped to manage time activities and positively stimulate students’ behavior, turning it into a powerful teaching strategy that contributed to boosting students' class disposition, favoring the creation of a positive learning environment, and concordant to this, it was evidenced that the greater the disposition, the closer to collaboration. The conclusion is that the music-mediated teaching strategies, based on needs, helped to create positive learning environments that were pleasant and stimulating for the students. The teaching strategies mediated by music also led to the development of collaborative learning, indicating that students assume roles and responsibilities when they work in groups, resulting in meaningful interactions that generate new knowledge.